ISSUES OF LINGUOPOETICS IN WORLD LINGUISTICS - Ashurova Zulkhumor (Social science and innovation, 2023)
The study of lingvopoetics in the article is cited on the example of European and Russian linguistics. The method of linguopoetic analysis is the study of the interdependence of word and sentence meanings, the study of linguopragmatic, stylistic aspects. The article also mentions the study of linguopoetics in world and Russian linguistics, as well monographs